Populating Sub-entries in Dictionaries with Multi-word Unitsfrom Concordance Lines - Otlogetswe, Thapelo J. (Lexikos, 2009)
Abstract: Lexicography is primarily concerned with the representation of words and their senses in dic-tionaries. By words most dictionary users and lexicographers refer to a combination of characters delineated by spaces on both sides. This article discusses the weakness of this approach in the selection of dictionary en-tries. Through an inspection of concordance lines generated from a multi-million Setswana corpus, it is ar-gued and demonstrated how multi-word units (MWUs), also known as multi-word expressions (MWEs), may be extracted from concordance lines to supplement dictionary entries. It is illustrated how both mono-lingual and bilingual Setswana dictionaries may be enhanced by the addition of MWEs as sub-entries. Keywords: SETSWANA, LEXICOGRAPHY, MULTI-WORD UNIT, CORPUS, CONCOR-DANCE, MULTI-WORD EXPRESSION, COLLOCATION, WORD, SUB-ENTRIES, DICTIONARY Opsomming: Die aanvulling van subinskrywings in woordeboeke met meerwoordige eenhede uit konkordansiereëls. Leksikografie is hoofsaaklik gemoeid met die weergawe van woorde en hul betekenisse in woordeboeke. Met woorde verwys die meeste woordeboekgebruikers en leksikograwe na ’n kombinasie van lettertekens afgegrens deur spasies aan beide kante. Hierdie artikel bespreek die swakheid van hierdie benadering by die keuse van woordeboekinskrywings. Deur ’n ondersoek van konkordansiereëls gegenereer uit ’n multimiljoen-Setswanakorpus, word daar geredeneer en verduidelik hoe meerwoordige eenhede (MWE’s), ook bekend as meerwoordige uitdrukkings (MWU’s), uit konkordansiereëls onttrek kan word om woordeboekinskrywings aan te vul. Daar word aangetoon hoe sowel eentalige as meertalige Setswanawoordeboeke uitgebrei kan word deur die toevoeging van MWU’s as subinskrywings. Sleutelwoorde: SETSWANA, LEKSIKOGRAFIE, MEERWOORDIGE EENHEID, KORPUS, KONKORDANSIE, MEERWOORDIGE UITDRUKKING, KOLLOKASIE, WOORD, SUBINSKRY-WINGS, WOORDEBOEK